2014
DOI: 10.4103/0973-1296.139793
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effect of Artemisiae annuae herba in lipopolysaccharide-stimulated RAW 264.7 Cells

Abstract: Background:Artemisiae annuae herba (AAH) has been traditionally used as a drug for the treatment of malaria, heat stroke, bacterial infection, and fever in East-Asia. Although AAH has been used for the treatment of inflammation-related symptoms, the underlying mechanism of antiinflammatory activity of AAH is still unknown.Objective:We investigated whether AAH have an inhibitory effect on the production of pro-inflammatory mediators in lipopolysaccharide-stimulated RAW 264.7 macrophage cells.Materials and Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Moreover, these extracts inhibited the nuclear translocation of p65 and I κ B α degradation in the NF- κ B pathway and decreased the extracellular signal-regulated kinase, p38, and c-Jun NH2-terminal kinase phosphorylation in the MAPK signaling pathway. These extracts possess the anti-inflammatory activities derived from the repression on the activation of NF- κ B and MAPKs pathways [ 61 ].…”
Section: Role Of Antioxidants In Inflammationmentioning
confidence: 99%
“…Moreover, these extracts inhibited the nuclear translocation of p65 and I κ B α degradation in the NF- κ B pathway and decreased the extracellular signal-regulated kinase, p38, and c-Jun NH2-terminal kinase phosphorylation in the MAPK signaling pathway. These extracts possess the anti-inflammatory activities derived from the repression on the activation of NF- κ B and MAPKs pathways [ 61 ].…”
Section: Role Of Antioxidants In Inflammationmentioning
confidence: 99%
“…Artemisinin is a sesquiterpene lactone and phytochemical found naturally in A. annua L.[ 1 ] Evidence for artemisinin's benefit was strongest for anti-malaria, anti-oxidative, anti-inflammatory, and anti-cancer effects. [ 4 5 ] It is reported that the anti-cancer effect of artemisinin in the presence of iron sources such as transferrin was increased several fold.…”
Section: Discussionmentioning
confidence: 99%
“…Artemisinin [ Figure 1 ], as a sesquiterpene lactone, found in sweet wormwood ( Artemisia annua L.), and it possesses a range of biological and medicinal properties, including anti-malaria and anti-cancer activities. [ 1 ] However, the hydrophobicity of artemisinin and its nonselective targeting toward cancer cells could limit its biomedical use. [ 2 ] It has been documented that cancer cells in the presence of transferrin were more susceptible to artemisinin cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…[ 10 ] TNF-α suppression has been studied as an approach to develop anti-inflammatory agents. [ 11 12 ] On the other hand, since it can induce apoptosis leading to tumor necrosis and regression, it has been considered as a candidate for cancer immunotherapy. [ 13 ] However, TNF-α, when administered systemically can cause severe adverse effects that are capillary leakage, disseminated coagulopathy, acidosis, and shock.…”
Section: Tnferade Biologymentioning
confidence: 99%